Применение ледовых конструкций в освоении Арктики : выпускная квалификационная работа магистра : The use of ice structures in the development of the Arctic - Гаврильев, Иван (Санкт-Петербургский политехнический университет Петра Великого, 2019)
Магистерская диссертация посвящена применению ледовых конструкций для освоения Арктики. Объект исследования: ледовые конструкции. В ходе исследования произведен анализ применения ледовых конструкций, проведены лабораторные испытания по определению прочности материала из ледобетона с различными армирующими материалами и добавками, подобрана плита покрытия из ледобетона, имеющая рациональную арочную форму на основании расчетов. Предложен способ повышения долговечности ледовых конструкций путем использования охлаждающих труб, по которым циркулирует хладагент. Разработана технология строительства зданий из ледобетона, произведен теплотехнический расчет ограждающих конструкций. Составлена локальная смета на строительство здания из ледобетона, предложены способы доставки материалов и оборудования до места строительства. Разработаны практические рекомендации по строительству и эксплуатации зданий из ледобетона. : Master's thesis is devoted to the use of ice structures for the development of the Arctic. Object of study: ice structures. The study analyzed the use of ice structures, conducted laboratory tests to determine the strength of the material of ice concrete with various reinforcing materials and additives, selected a plate of ice concrete with a rational arch shape based on the calculations. A method is proposed for increasing the durability of ice structures by using cooling pipes through which the refrigerant circulates. A technology has been developed for the construction of buildings made of ice concrete; a heat engineering calculation has been made for enclosing structures. A local estimate for the construction of an ice concrete building was drawn up, and methods for the delivery of materials and equipment to the construction site were proposed. Developed practical recommendations for the construction and operation of buildings of ice concrete.